2011
DOI: 10.1038/npp.2011.315
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Neural Progenitors in the Hippocampus Predict Memory Impairment and Relapse to Drug Seeking as a Function of Excessive Methamphetamine Self-Administration

Abstract: Methamphetamine affects the hippocampus, a brain region crucial for learning and memory, as well as relapse to drug seeking. Rats self-administered methamphetamine for 1 h twice weekly (intermittent-short-I-ShA), 1 h daily (limited-short-ShA), or 6 h daily (extended-long-LgA) for 22 sessions. After 22 sessions, rats from each access group were withdrawn from self-administration and underwent spatial memory (Y-maze) and working memory (T-maze) tests followed by extinction and reinstatement to methamphetamine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 85 publications
(117 reference statements)
3
96
1
Order By: Relevance
“…Considering that OXR1 has a higher affinity for orexin A than orexin B, these results suggest that the functional adaptation of DG neurons via OXR1 plays a critical role in the addictive behaviors associated with morphine. This was consistent with the previous finding that the change of neuronal activation in the DG affected addiction-related behaviors (Ricoy & Martinez 2009;Recinto et al 2012). Orexinergic neurons also produced other neurotransmitters, such as dynorphin, pentraxin and glutamate, which may influence addiction-related behaviors (Chou et al 2001;Reti et al 2002;Rosin et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Considering that OXR1 has a higher affinity for orexin A than orexin B, these results suggest that the functional adaptation of DG neurons via OXR1 plays a critical role in the addictive behaviors associated with morphine. This was consistent with the previous finding that the change of neuronal activation in the DG affected addiction-related behaviors (Ricoy & Martinez 2009;Recinto et al 2012). Orexinergic neurons also produced other neurotransmitters, such as dynorphin, pentraxin and glutamate, which may influence addiction-related behaviors (Chou et al 2001;Reti et al 2002;Rosin et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Similar effects were found after the animals were trained by the Morris water maze, after nicotine treatment [61]. Self-administration, a form of operant conditioning considered to be one of the most valid experimental models to investigate addiction-related behavior, may also induce detectable alterations in neurogenesis in response to various addictive drugs such as opioids [36], methamphetamine [21, 62] and nicotine [63]. Similar results were shown in a study of alcohol addiction using the voluntary drinking paradigm, which confirmed a decrease in neuronal differentiation [64].…”
Section: Experimental Methods and Paradigmsmentioning
confidence: 73%
“…By quantifying 2-h-old SGZ BrdU-positive cells, it was clear that chronic methamphetamine administration decreased the number of new hippocampal NSPCs in rats. By contrast, protracted withdrawal of methamphetamine promoted the proliferation of SGZ cells and restored the survival of impaired cells after chronic methamphetamine self-administration [62]. The in vivo findings indicating the anti-proliferation role of methamphetamine were further supported by in vitro studies using adult hippocampal progenitor cells, which found that the number of neurospheres decreased by methamphetamine treatment in a dose- and time-dependent manner [39, 113].…”
Section: Modulation Of Nspcs By Addictive Drugs and Underlying Mechanmentioning
confidence: 99%
“…Withdrawal from methamphetamine self-administration enhances methamphetamine seeking following priming in animals given extended access (but not limited access) to methamphetamine self-administration, suggesting that the magnitude of methamphetamine seeking is directly related to the amount of intake during prolonged methamphetamine self-administration (Yan et al, 2007; Rogers et al, 2008; Recinto et al, 2012). Furthermore, enhanced methamphetamine seeking following withdrawal correlated with increases in neuronal activation in the mPFC (Recinto et al, 2012). This suggests that alterations in glial plasticity produced by methamphetamine may impact the activation of neurons in the mPFC (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that alterations in glial plasticity produced by methamphetamine may impact the activation of neurons in the mPFC (Kim et al, 2014). Some recent advances have been made to determine whether withdrawal from methamphetamine differentially influences the proliferation and survival of progenitors in the hippocampus when compared with methamphetamine exposure (Recinto et al, 2012). Emerging evidence demonstrates that withdrawal from methamphetamine enhances proliferation and survival of newly born progenitors in the hippocampus, and enhanced survival of progenitors could be responsible for the enhanced neurogenesis during protracted withdrawal after methamphetamine (or cocaine) self-administration (Noonan et al, 2008; Deschaux et al, 2012; Recinto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%